CLUSTER ANALYSIS OF HIGHEST EDUCATION COMPLETED IN EAST JAVA PROVINCE WITH SPHERICAL K-MEANS METHOD - Purnama, Mohammad Dian (Parameter: Journal of Statistics, 2025)
One of the key pillars of development that greatly aids in the social and economic advancement of civilization is education. The purpose of this study is to use the Spherical K-Means Clustering method to evaluate the distribution and degree of educational attainment in districts/cities in East Java Province. This approach was selected because it can group vector-based data according to directional similarity, making it appropriate for multidimensional data. Based on education-related variables, including never attending school, not graduating from primary school, graduating from primary school, graduating from junior high school, graduating from senior high school, and graduating from university, this analysis groups regions. Based on the clustering results, several significant clusters were found. Areas with strong secondary and tertiary education levels make up Cluster 1. There is a more equitable distribution of schooling between primary and secondary education in Cluster 2. Regions with a higher percentage of basic education and lower secondary education levels are included in Cluster 3. The results can help stakeholders create more focused and efficient education policies by offering significant insights into the differences in educational attainment in East Java.